The Long Road To 64 Bits. - MASHEY, JOHN (Communications of the ACM, 2009)
The article discusses the development of computers, examining the chronology of transitions in the computer industry from 32-bit and 64-bit microprocessor systems. Future software will be effected by decisions made in the past, decisions that have unintended consequences and side effects that last for decades, the author states. Topics include running out of address space, the predictability of Moore's Law, and customers that are unable to use computer memory they can afford. Also discussed is the usage of C data types.